2015
DOI: 10.1242/dev.119685
|View full text |Cite
|
Sign up to set email alerts
|

teashirt is required for head-versus-tail regeneration polarity in planarians

Abstract: Regeneration requires that the identities of new cells are properly specified to replace missing tissues. The Wnt signaling pathway serves a central role in specifying posterior cell fates during planarian regeneration. We identified a gene encoding a homolog of the Teashirt family of zinc-finger proteins in the planarian Schmidtea mediterranea to be a target of Wnt signaling in intact animals and at posterior-facing wounds. Inhibition of Smed-teashirt (teashirt) by RNA interference (RNAi) resulted in the rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 69 publications
(111 reference statements)
6
35
0
Order By: Relevance
“…RNAi of beta-catenin-1 [at a time of regeneration prior to bodywide formation of ectopic anterior central nervous system structures (Gurley et al, 2008;Iglesias et al, 2008;Petersen and Reddien, 2008)] caused a decrease in brain size in heads regenerated from anterior-facing wounds (Fig. 4C), opposite to the wnt11-6 RNAi phenotype and consistent with previous findings (Owen et al, 2015). wnt11-6(RNAi);beta-catenin-1(RNAi) animals had large brains similar to wnt11-6 inhibition alone (Fig.…”
Section: Planarians Robustly Restore Brain:body Proportionality Throusupporting
confidence: 89%
“…RNAi of beta-catenin-1 [at a time of regeneration prior to bodywide formation of ectopic anterior central nervous system structures (Gurley et al, 2008;Iglesias et al, 2008;Petersen and Reddien, 2008)] caused a decrease in brain size in heads regenerated from anterior-facing wounds (Fig. 4C), opposite to the wnt11-6 RNAi phenotype and consistent with previous findings (Owen et al, 2015). wnt11-6(RNAi);beta-catenin-1(RNAi) animals had large brains similar to wnt11-6 inhibition alone (Fig.…”
Section: Planarians Robustly Restore Brain:body Proportionality Throusupporting
confidence: 89%
“…As in intact animals, β-CATENIN-1 is active both ventrally, where the brain primordium forms, and dorsally, in anterior regenerating blastemas. In accordance with this complex pattern of activity, our findings show that β-catenin-1 is required to regenerate a normal sized brain, with the correct number of neural cell populations, as well as a normal head sensory margin (Hill and Petersen, 2015;Owen et al, 2015). Importantly, the midline ventral furrow and notum expression in the anterior midline also disappears in β-catenin-1 (RNAi) animals, which suggest a problem in anterior tip patterning and the establishment of the anterior organizing region.…”
Section: β-Catenin-1 Controls Anterior Patterningsupporting
confidence: 74%
“…notum and sFRP) localize to the anterior pole, and their inhibition leads to anteriorized or posteriorized phenotypes, respectively (Adell et al, 2009;Gurley et al, 2010;Lander and Petersen, 2016;Reddien, 2009b, 2011;Scimone et al, 2016;Sureda-Gómez et al, 2015). Interestingly, recent reports have suggested that β-catenin-1 exerts additional roles in eye and brain patterning (Hill and Petersen, 2015;Owen et al, 2015), which is consistent with the ubiquitous mRNA expression of β-catenin-1 (Gurley et al, 2008;Iglesias et al, 2008;Petersen and Reddien, 2008). To date, however, no studies have described the localization of β-CATENIN-1 protein either as an AP gradient or in specific developing tissues.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations